Schizophrenia and common sense: explaining the relation between madness and social values - Hipólito, Inês; Gonçalves, Jorge; Pereira, João G. (Studies in brain and mind, 2018)
This book explores the relationship between schizophrenia and common sense. It approaches this theme from a multidisciplinary perspective. Coverage features contributions from phenomenology, cognitive neuroscience, philosophy of mind, psychology, and social cognition. The contributors address the following questions: How relevant is the loss of common sense in schizophrenia? How can the study of schizophrenia contribute to the study of common sense? How to understand and explain this loss of common sense? They also consider: What is the relationship of practical reasoning and logical formal reasoning with schizophrenia? What is the relationship between the person with a diagnosis of schizophrenia and social values? Chapters examine such issues as rationality, emotions, self, and delusion. In addition, one looks at brain structure and neurotransmission. Others explore phenomenological and Wittgensteinian theories. The book features papers from the Schizophrenia and Common Sense International Workshop, held at New University of Lisbon, November 2015. It offers new insights into this topic and will appeal to researchers, students, as well as interested general readers